2011
DOI: 10.2217/pmt.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and Pain Management: Current Trends and Future Directions

Abstract: SUMMARY Virtual reality (VR) has been used to manage pain and distress associated with a wide variety of known painful medical procedures. In clinical settings and experimental studies, participants immersed in VR experience reduced levels of pain, general distress/unpleasantness and report a desire to use VR again during painful medical procedures. Investigators hypothesize that VR acts as a nonpharmacologic form of analgesia by exerting an array of emotional affective, emotion-based cognitive and attentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
275
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(308 citation statements)
references
References 55 publications
(64 reference statements)
7
275
0
7
Order By: Relevance
“…Our literature findings, however, on the use of VR technology in pain research seem to be consistent with the studies reported in a recent comprehensive review of the literature performed by Li et al [31]. In all, these findings seem to raise three important points that need to be further addressed:…”
Section: Resultssupporting
confidence: 92%
“…Our literature findings, however, on the use of VR technology in pain research seem to be consistent with the studies reported in a recent comprehensive review of the literature performed by Li et al [31]. In all, these findings seem to raise three important points that need to be further addressed:…”
Section: Resultssupporting
confidence: 92%
“…The VRD condition significantly increased the pain threshold in comparison with the control condition. Overall, therefore, both interventions have some effects on pain-related variables, a finding that is consistent with previous studies 1,4 and with our own results in earlier experiments involving the same interventions. [20][21][22] Notably, however, neither of the two interventions had any effect on pain intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, people enjoy using VR and are keen to use it again during other painful medical procedures. [1][2][3] The effects of VR have been mainly explained in terms of pain distraction. Since attentional resources are limited, diverting attention away from pain by means of VR leaves fewer resources available for pain processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedback-based strategies are mainly used for phantom limb pain or complex regional pain syndrome. [2][3][4][5] Based on a recent meta-analysis of 14 controlled studies, VR-induced distraction has been indicated highly effective in alleviating pain. 6 This analysis found a mean weighted effect size of 0.90 for VR distraction but it was not possible to draw any conclusion of VR effectiveness for acute versus chronic pain conditions.…”
mentioning
confidence: 99%